Binding force of extended continental shelf limits: investigating whether Article 76(8) of UNCLOS constitutes customary international law - Mao, Zhengkai; Li, Xiaohan; Liu, Huirong; Zhang, Zhijun (Frontiers in Marine Science, 2023)
International custom is considered to be the oldest and the original source of public international law.However, because it is unwritten, the identification of international custom has always been a controversial issue in the context of international law. Article 76(8) of the United Nations Convention on the Law of the Sea (UNCLOS) is the core article of the international system of laws governing the continental shelf. It stipulates the basic procedure for identifying the rights of coastal states to the continental shelf beyond 200 nautical miles (extended continental shelf, ECS) The issue of whether this paragraph constitutes customary international law is actually the question of whether the binding force of the limits of the ECS, which have been delineated based on recommendations of the Commission on the Limits of the Continental Shelf, can extend to non-parties to the UNCLOS. This study starts with the "two elements" theory of traditional customary international law and then considers its new interpretation according to modern theories. Following this, the authors provide a jurisprudential and practical exploration of whether Article 76(8) of the UNCLOS constitutes customary international law from the perspectives of how treaties are used to form customary international law, and the current delineation practices of coastal states on the ECS.